2021
DOI: 10.3390/jpm11111087
|View full text |Cite
|
Sign up to set email alerts
|

Individualized 3D-Printed Bone-Anchored Maxillary Protraction Device for Growth Modification in Skeletal Class III Malocclusion

Abstract: Bone-anchored maxillary protraction (BAMP) is effective for skeletal Class III malocclusion. However, infection, screw and plate loosening, and device failures occur with conventional plates. This pilot prospective study analyzed the feasibility of individualized BAMP using preoperative simulation and 3D titanium printing in patients referred by the orthodontic department for four BAMP miniplates. Preoperative cone beam computed tomography data were analyzed using CAD/CAM software to fabricate the individualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“… 100 % None reported 15. Kim et al (2021) Pilot Controlled clinical trials The feasibility of individualized bone-anchored maxillary protraction using preoperative simulation and 3D titanium printing was being analyzed. Bone-anchored maxillary protraction CBCT and intraoral scanning 24 months Preoperative simulation and 3D titanium printing allowed for the precise fabrication and placement of customized BAMP devices.…”
Section: Resultsmentioning
confidence: 99%
“… 100 % None reported 15. Kim et al (2021) Pilot Controlled clinical trials The feasibility of individualized bone-anchored maxillary protraction using preoperative simulation and 3D titanium printing was being analyzed. Bone-anchored maxillary protraction CBCT and intraoral scanning 24 months Preoperative simulation and 3D titanium printing allowed for the precise fabrication and placement of customized BAMP devices.…”
Section: Resultsmentioning
confidence: 99%
“…The mini-plates were designed according to maxillary bone anatomy and the position of the roots and then 3D printed by selective laser melting (SLM) of titanium powder [ 14 ]. Similarly, Kim et al [ 8 ] used a customized bone-anchored maxillary protraction device, 3D printed in a titanium alloy with SLS, to hook intermaxillary elastics in the treatment of two patients with Class III malocclusion. Graf et al [ 15 ] showed that a digital workflow involving intraoral digital scan, digital design, direct 3D metal printing via SLM (Concept Laser, Lichtenfels, Germany), and laser welding could be efficient for constructing Hyrax-type rapid palatal expanders (RPEs), also supported by mini-implants [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has also been claimed that 3D printing provides greater opportunities for the customization of intraoral and extraoral devices [ 1 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…CAD/CAM technology has enabled preoperative virtual simulation according to the treatment plan [ 5 ], while 3D printing technology plays a role in the application of virtual preoperative simulation to the surgical field. In addition, 3D-metal printing using selective laser sintering allows the fabrication of individualized bone fixation plates and bone reconstruction materials [ 6 , 7 ]. Although several studies have described computer-assisted virtual planning for orthognathic surgeries [ 8 - 11 ], the accurate application of the prefabricated device to the determined location during surgery remains a challenge, as does the lack of any evaluation of the effectiveness and accuracy of the 3D-printed plates and osteotomy guides to ensure they are correct for surgical implementation.…”
Section: Introductionmentioning
confidence: 99%